MEASURING THE ROTATION RATES OF WOLF-RAYET STARS FROM LARGE-SCALE WIND VARIABILITY - N. St-Louis (Revista Mexicana de Astronomía y Astrofísica, 2008)
The rotational velocity of Wolf-Rayet (WR) stars cannot be measured directly from "classical" photospheric absorption lines. However, it can be infered from periodic large-scale wind variability.Afteridentifying a list of WR stars presenting large-scale spectral variability, we have monitored 3 of them intensively. The period of these stars, along with the already published periods of WR6 and WR134, lead to a rotational velocity for WR stars in the range of 10-60 km s-1.